Respostas
respondido por:
0
2)
f(x)=x²+2x-4, para x=4
f(4)=(4)²+2(4)-4
f(4)=16+8-4
f(4)=20
f(3)=(3)²+2(3)-4
f(3)=9+6-4
f(3)=11
f(2)=(2)²+2(2)-4
f(2)=4+4-4
f(2)=4
20-11/4
9/4= 2,25
3)
x²-2x-3
∆=(-2)²-4(1)(-3)
∆=4+12
∆=16
∆>0: duas raízes reais e diferentes; com a parábola para cima, pois a>0
b) -x²+4x
parábola para baixo, pois a<0
-x²+4x=0(-1)
x²-4x
x(x-4)
x=0
x=4; duas raízes reais e diferentes
f(x)=x²+2x-4, para x=4
f(4)=(4)²+2(4)-4
f(4)=16+8-4
f(4)=20
f(3)=(3)²+2(3)-4
f(3)=9+6-4
f(3)=11
f(2)=(2)²+2(2)-4
f(2)=4+4-4
f(2)=4
20-11/4
9/4= 2,25
3)
x²-2x-3
∆=(-2)²-4(1)(-3)
∆=4+12
∆=16
∆>0: duas raízes reais e diferentes; com a parábola para cima, pois a>0
b) -x²+4x
parábola para baixo, pois a<0
-x²+4x=0(-1)
x²-4x
x(x-4)
x=0
x=4; duas raízes reais e diferentes
Anônimo:
Obrigado !
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás